2015
DOI: 10.5120/21176-4185
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Sentiment Analysis in Hindi using HSWN

Abstract: Due to increase in amount of Hindi content on the web in past years, there are more requirements to perform sentiment analysis for Hindi Language. Sentiment Analysis (SA) is a task which finds orientation of one's opinion in a piece of information with respect to an entity. It deals with analyzing emotions, feelings, and the attitude of a speaker or a writer from a given piece of information. Sentiment Analysis involves capturing of user's behavior, likes and dislikes of an individual from the text. The work o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Pandey et al [13] defined a framework to carry out the SA task on the Hindi movie reviews. [13] observed that the lower accuracy was obtained by using SWN as a classification technique and hence suggested using synset replacement algorithm along with the SWN. Synset replacement algorithms groups the synonymous words having same concepts together.…”
Section: Sentence Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…Pandey et al [13] defined a framework to carry out the SA task on the Hindi movie reviews. [13] observed that the lower accuracy was obtained by using SWN as a classification technique and hence suggested using synset replacement algorithm along with the SWN. Synset replacement algorithms groups the synonymous words having same concepts together.…”
Section: Sentence Levelmentioning
confidence: 99%
“…Synset replacement algorithms groups the synonymous words having same concepts together. It helped in increasing the accuracy of the system because if the word was not present in the Hindi SWN then it found the closest word and assigned the score of that word [13]. In the study, Bhargava et al [14] completed the SA task on the FIRE 2015 dataset.…”
Section: Sentence Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…It manages examining individual feelings, sentiments, state of mind and conclusion of a speaker or an author over a question. The essential focus of SA is to discover the assessments communicated by individual over a data or element [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nagesh and Ravi [26] gave a way to perform language identification using multi class regression classifiers and was able to get nearly 54% accuracy. Pandey and Sharvari [27] applied HSWN along with negation discourse for sentiment analysis of Hindi language text corpora, with the accuracy of near 80%. Srinivas, Sharma and Balbantray [28] demonstrated that text normalization can be achieved using techniques such phonetics based, slang and spelling correction approaches in another limited work [29] they demonstrated application of sentiment analysis techniques on transliterated text by using bilingual dictionary methods and HSWN for sentiment score calculation with 80% accuracy being achieved.…”
Section: Balamurali and Joshimentioning
confidence: 99%